2009
DOI: 10.1074/jbc.m109.029926
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Stoichiometry of T4 Bacteriophage Helicase Loader Protein (gp59)

Abstract: The T4 bacteriophage helicase loader (gp59) is one of the main eight proteins that play an active role in the replisome. gp59 is a small protein (26 kDa) that exists as a monomer in solution and in the crystal. It binds preferentially to forked DNA and interacts directly with the T4 helicase (gp41), singlestranded DNA-binding protein (gp32), and polymerase (gp43). However, the stoichiometry and structure of the functional form are not very well understood. There is experimental evidence for a hexameric structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…D, reactions were repeated using the same conditions and the same range of concentrations as in C except that the Gp59 was removed from the reaction. Gp59 to etheno-modified ssDNA and 2-aminopurine-labeled fork DNAs as well as hexamer formation on fork DNA (13,21,33). The presence of the Alexa Fluor 546 label significantly stabilizes Gp59-DNA interactions because fluorescence quenching of labeled fork, ssDNA, or dsDNA was not reduced by the addition of equimolar unlabeled DNA (data not shown).…”
Section: Detection Of Hlc Formation and Dependence On Ssdnamentioning
confidence: 94%
“…D, reactions were repeated using the same conditions and the same range of concentrations as in C except that the Gp59 was removed from the reaction. Gp59 to etheno-modified ssDNA and 2-aminopurine-labeled fork DNAs as well as hexamer formation on fork DNA (13,21,33). The presence of the Alexa Fluor 546 label significantly stabilizes Gp59-DNA interactions because fluorescence quenching of labeled fork, ssDNA, or dsDNA was not reduced by the addition of equimolar unlabeled DNA (data not shown).…”
Section: Detection Of Hlc Formation and Dependence On Ssdnamentioning
confidence: 94%
“…Small angle x-ray scattering analysis of a gp59/SSB heterodimer agrees with the gp59/ SSB contact (36). It should be noted that single molecule photobleaching experiments have suggested that the active form of gp59, like that of helicase, is a hexamer (35). Thus, it may be that each monomer of gp59 makes contact with individual monomers of helicase and/or SSB.…”
Section: Discussionmentioning
confidence: 99%
“…, 2011), transmembrane α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor-regulatory proteins (Hastie et al. , 2013), T4 bacteriophage helicase loader protein (Arumugam et al. , 2009), bacterial oxidative phosphorylation complexes (Llorente-Garcia et al.…”
Section: Introductionmentioning
confidence: 99%